1996
DOI: 10.1115/1.2804886
|View full text |Cite
|
Sign up to set email alerts
|

Verification of a Cohesive Zone Model for Ductile Fracture

Abstract: In the present paper, ductile crack growth in an aluminium alloy is numerically simulated using a cohesive zone model under both plane stress and plane strain conditions for two different fracture types, shear and normal modes. The cohesive law for ductile fracture consists of two parts—a specific material’s separation traction and energy. Both are assumed to be constant during ductile fracture (stable crack growth). In order to verify the assumed cohesive law to be suitable for ductile fracture processes, exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…These are, however, encouraging as Li and Siegmund [77] have shown for the cohesive zone approach and Kim et al [139] for a modified Gurson approach.…”
Section: Figure 29mentioning
confidence: 85%
See 2 more Smart Citations
“…These are, however, encouraging as Li and Siegmund [77] have shown for the cohesive zone approach and Kim et al [139] for a modified Gurson approach.…”
Section: Figure 29mentioning
confidence: 85%
“…Li and Siegmund, in [77] showed that the CTOA, instead of being constant, reduces rapidly when the crack tips start to interact and falls even to zero during the link up. That means that the parameter can be used only as long as no interaction between the crack tips takes place which is, however, sufficient for many practical applications.…”
Section: Figure 29mentioning
confidence: 99%
See 1 more Smart Citation
“…Cohesive models [8,9] allow for separation of interfaces between continuum elements, if some critical value of a separation is reached locally, whereas the material outside deforms according to elasto-plastic constitutive equations without any damage. The so-called process zone is a material volume, and material separation and fracture are controlled by a cohesive law, which has the general form σ = f(δ), where δ = [u] is the corresponding value of the displacement jump between adjacent continuum elements.…”
Section: Introductionmentioning
confidence: 99%
“…Various functions exist for the cohesive law [8][9][10], which have in common, that they contain two characteristic parameters (per fracture mode), a cohesive strength, σ 0 , and a critical separation, δ c . The cohesive law proposed by Scheider [12], …”
Section: Introductionmentioning
confidence: 99%